The antibacterial activity of honey against bacteria / Izyan A. Wahab - A. Wahab, Izyan (2005)
Samples of natural pure honey from two different plants were studied for their antimicrobial activities against bacteria strains isolated from human pathology obtained from Hospital Kuala Lumpur. The plants were: 2 samples from Tualang tree and 1 sample from multifloral sources. All samples were obtained from different places in Pahang, Malaysia. Honeys with different concentrations (100% v/v, 50% v/v, 25% v/v, 12.5% v/v and 6.25% v/v) were tested on the bacteria strains using the disc diffusion method and the agar well diffusion method. The bacterial strains that were used are, Staphylococcus aureus. Methicillin Resistant Staphylococcus Aureus (MRSA), Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae. Results revealed that in disc diffusion assay, S. aureus and E. coli were inhibited by honey at 50% v/v and 100% v/v concentration for all honey samples. In agar well diffusion assay, S.aureus, E. coli and MRSA were sensitive to honey. For S.aureus and E. coli, all the strains were inhibited by all honey samples at, 25% v/v, 50% v/v and 100% honey concentration. For MRSA, only one honey samples show inhibition zone, honey samples from Tualang tree and got inhibited by 12.5% v/v, 25% v/v and 50% v/v honey concentration. When compared to the inhibition zones produced by the commercial antibiotics, the antibiotics were still greater than the honey in terms of clear visible inhibition zone produced. The results also showed that there was a difference in terms of antibacterial activities to different bacterial strains among the different origin of honey (plants).